Terapi Kelompok Ulasan Hidup Dapat Meningkatkan Harga Diri Lansia - Adelia Rochma; Retno Lestari; Lilik Supriati (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2021)
Introduction: Changes in the self-esteem of the elderly often occur with the emergence of feelings of worthlessness, worthlessness, lack of confidence, and withdrawal from their environment. The impact of changes in self-esteem will trigger depression as well as reduce the quality of life of the elderly. Life review therapy that is carried out in groups for the elderly can increase positive perceptions through stories and life experiences of all members of the elderly group. Objective: This study was conducted to determine the effect of life review group therapy in increasing the self-esteem of the elderly. Method: The pre-experimental one-group pretest-posttest design without a control group was used in this study. Through the purposive sampling technique, the number of samples obtained is 25 elderlies. Elderly self-esteem was assessed using the Rosenberg Self-Esteem Scale (RSES) instrument. Results and discussion: The results of the study which were tested with Wilcoxon Matched-Pairs showed that there was an effect of self-esteem before and after being given life review group therapy worth p = 0.000 < 0.05. Life review group therapy helps the elderly to remember experiences in the past, about parents and siblings in childhood, adolescence, and positive experiences they have had. In addition to remembering their past experiences, the elderly is invited to analyze and evaluate these experiences and help them change their negative perceptions into positive ones. Conclusion: It can be concluded that life review group therapy has a positive effect on the self-esteem of the elderly. Therefore, life review group therapy can be used as an alternative to increasing the self-esteem of the elderly.